Sulphur, boron and zinc nutrition to improve productivity, profitability and oil quality in sunflower (Helianthus annuus) - SHEORAN, PARVENDER; SARDANA, V; CHANDER, S; KUMAR, A; MEENA, M D; BALI, A; SHARMA, P (The Indian Journal of Agricultural Sciences, 2018)
Yield response, profitability margins and oil quality in relation to macro (S) and micro (B and Zn) nutrients application with NPK recommendations were quantified in spring planted sunflower (Helianthus annuus L.). Significantly higher seed yield, synergism in nutrients uptake and superior oil quality was noticed through better expression of physio-morphic traits and yield components, increased nutrient accumulation and improvement in oil quality parameters with application of S, B and Zn. Supplemented nutrition proved to be economically more efficient and sustainable over recommended NPK as evident by relatively higher crop yield response (0.10-0.18 t ha-1), production efficiency (4.7-8.0%), profitability (0.50-0.97 USD/ha/day), relative economic efficiency (4.64- 9.05%) and sustainability yield index (5.1-8.5%). Improvement in saturated fatty acid (SFA): unsaturated fatty acid (UFA) ratio indicated improvement in oil quality, followed the trend of S>B=Zn. An inverse correlation (r = –0.68**) between mono- (oleic) and poly- (linoleic) unsaturated fatty acids indicated the inter-dependence of these two quality parameters. The information generated would facilitate quantitative yield predictions in relation to macro (S) and micro (B and Zn) nutrient application with recommended fertilization in sunflower.